THE SCIENTIFIC RATIONALE FOR THE PROBLEM OF PREDICTION OF THE NATURE AND EXTENT OF THE DESTRUCTION OF THE RAILWAYS FOR A SPECIAL PERIOD - Fesenko, M. V.; Radkevych, A. V. (Science and Transport Progress, 2007)
The article considers a series of separate tasks, which are to be solved for substantiation of the military-scientific task, prognostication of the character and scale of railways destruction for the special period.